Computational and mutational analysis of TatD DNase of Bacillus anthracis. Issue 7 (5th February 2019) - Singh, Damini; Rahi, Amit; Kumari, Romika; Gupta, Vatika; Gautam, Gunjan; Aggarwal, Somya; Rehan, Mohd; Bhatnagar, Rakesh
Abstract: The role of TatD DNases as DNA repair enzymes or cell death (apoptotic) nucleases is well established in prokaryotes as well as eukaryotes. The current study aims to characterize the TatD nuclease from Bacillus anthracis (Ba TatD) and to explore its key histidine catalytic residues. Ba TatD was found to be a metal‐dependent, nonspecific endonuclease which could efficiently cleave double‐stranded DNA substrates. Moreover, Ba TatD nuclease was observed to be thermostable up to 55°C and act in a wide pH range indicating its industrial applicability. Diethyl pyrocarbonate‐based histidine‐selective alkylation of the Ba TatD resulted in a loss of its nuclease activity suggesting a crucial role of the histidine residues in its activity. The key residues of Ba TatD were predicted using sequence analysis and structure‐based approaches, and then the predicted residues were further tested by mutational analysis. Upon mutational analysis, H128 and H153 have been found to be crucial for Ba TatD activity, though H153 seems to bear an important but a dispensable role for the Ba TatD nuclease. Ba TatD had a uniform expression in the cytosol of B. anthracis, which indicates a significant role of the protein in the pathogen's life cycle. This is the first study to identify and characterize the TatD DNase from B. anthracis and will be helpful in gaining more insights on the role of TatD proteins in Gram‐positive bacteria where it remains unexplored. Abstract : Crucial catalytic residues of TatD DNase of Bacillus anthracis are explored using computational sequence‐ and structure‐based methods followed by experimental mutational analysis. Two histidine residues, H128 and H153, have been found to be crucial for TatD activity. These residues are lying within the α/β barrel with side chains facing the central hollow core.